The effect of spiritual support on life satisfaction in Iranian patients with gastrointestinal cancer - Hamidi, Sajad; Seyedfatemi, Naeimeh; Abbasi, Zahra; Ebrahimpour, Fatemeh (Frontiers in Psychology, 2024)
Background The diagnosis and treatment of gastrointestinal cancer not only impose significant physical challenges but also deeply affect patients emotionally and psychologically, significantly influencing their overall quality of life. Among the various factors that can positively impact life satisfaction in individuals facing gastrointestinal cancer, spirituality emerges as a crucial aspect. This study aimed to determine the effect of a spiritual intervention on life satisfaction in patients with gastrointestinal cancer. Methods This quasi-experimental study was conducted with two groups of 85 gastrointestinal cancer patients from two major hospitals in Tehran. The intervention group received spiritual support through social media for six sessions over three weeks to learn how to effectively improve their spiritual state. The control group received routine medical visits and care. The Satisfaction with Life Scale (SWLS) was used before and after the spiritual support in both the intervention and control groups. The research was approved by the institutional ethics committee. Results In the pre-test stage, there was no significant difference in average life satisfaction between the intervention and control groups (t = 1.887, d = 0.30, p > 0.05). However, positive changes occurred in the post-test stage. Notably, the disparity in average life satisfaction between the intervention and control groups was significant in the post-test stage (t = 13.118, d = 0.95, p < 0.01). Furthermore, the result showed that the changes in life satisfaction in the intervention group were statistically significant (t = 11.854, d = 0.84, p < 0.001). Changes in life satisfaction in the control group were not statistically significant in the pre-test stage compared to the post-test stage (t = 1.113, d = 0.10, p > 0.05). Conclusion The results can guide health care providers in dealing with the problems of cancer patients. Assessing patients’ spiritual needs and empowering them to promote their spiritual recovery and find meaning in their suffering can lead to improved quality of life and satisfaction with holistic care.